2018
DOI: 10.1002/dac.3500
|View full text |Cite
|
Sign up to set email alerts
|

Analytical models for communication links in emergency management simulation

Abstract: Emergency response involves the management of several different types of critical infrastructures and resources. Because of the interdependent nature of these systems, it is often very difficult for human decision makers to determine what the second-or third-order effects of their decisions or actions might be. This has resulted in the development of several simulation tools that could be used to evaluate decisions or behaviours and better inform decision makers about the potential impacts of their decisions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Every decision taken will have a certain impact on the system that has been simulated (Buditjahjanto & Miyauchi, 2011). In line with that Adams and Singh (2018) indicated that some simulation tools with their learning content could be applied to evaluate decisions or behaviors to better supply information to decision-makers toward the potential impacts of their decisions.…”
Section: Introductionmentioning
confidence: 84%
“…Every decision taken will have a certain impact on the system that has been simulated (Buditjahjanto & Miyauchi, 2011). In line with that Adams and Singh (2018) indicated that some simulation tools with their learning content could be applied to evaluate decisions or behaviors to better supply information to decision-makers toward the potential impacts of their decisions.…”
Section: Introductionmentioning
confidence: 84%
“…This involves seeking feedback, evaluating strategies, and adapting practices to better meet the needs of diverse populations (Clark & Turner, 2020). Furthermore, advocating for policies and initiatives that promote equity and inclusion in communication is crucial (Adams & White, 2018). By prioritising equity, organisations and communities can create environments where everyone has the opportunity to participate, be heard, and contribute (Taylor & Harris, 2021).…”
Section: Communication Equity Inclusion and Language Diversitymentioning
confidence: 99%